Regulation of dendritic cell biology by amino acids and their transporters - Chen, Shanlin; Li, Gongwei; Jiang, Zihao; Xu, Yuekang; Aipire, Adila; Li, Jinyao (Frontiers in Immunology, 2025)
Dendritic cells (DCs) play a central role in inducing both immunity and tolerance as specialized antigen-presenting cells (APCs). The immunometabolic firestorm in recent years has focused our attention on how DCs use energy and respond to nutritional changes that affect immune functions. Like in every other cell, such metabolic events as the concentration of free amino acids, membrane-bound transporter proteins, key metabolic enzymes, and sensors (e.g., mTOR and GCN2), also profoundly affect the function and fate of DCs. Therefore, dysregulation of amino acid metabolism can cause metabolic reprogramming of DCs, leading to or accelerating the occurrence of various immunological disorders, like type 1 diabetes, rheumatoid arthritis, and cancer. Since amino acids cannot directly enter the cell to participate in metabolic activities, their transporters act as critical metabolic gatekeepers. To catch up with the rapid development in the immune metabolism field, this review summarized recent studies on the potential roles of different amino acids and their transporters in the regulation of DCs biology to offer new insights for immune-dysregulated diseases and explore new therapeutic targets.